2010
DOI: 10.1002/cyto.b.20526
|View full text |Cite
|
Sign up to set email alerts
|

CD203c‐based basophil activation test in allergy diagnosis: Characteristics and differences to CD63 upregulation

Abstract: Background:The basophil activation test (BAT) based on CD203c upregulation has been validated as a reliable tool for the diagnosis of IgE-mediated allergies. Nevertheless, CD203c-based BAT is hardly comparable with that of CD63-based tests, as the mechanisms of CD203c versus CD63 induction differ considerably. The aim of the present study was to identify potent influencing factors of the CD203c-based BAT and to emphasize differences between CD63 and CD203c detection.Methods: CD203c-based BAT was determined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 36 publications
2
78
0
7
Order By: Relevance
“…The test tubes are then rotated at 4°C and 200´g for 5 min. After the tubes are prepared, in order to select the basophil and measure the activity before starting to work in flow cytometry, the cells are stained with 20 μL monoclonal anti-human IgE, 10 μL monoclonal CD63, and 10 μL CD203C antibodies on ice for 20 min (9)(10)(11)(12)(13)(14). Then, the tubes are worked on in the flow cytometry.…”
Section: Basophil Activation Test: How Is the Activation Of In Vitro mentioning
confidence: 99%
See 1 more Smart Citation
“…The test tubes are then rotated at 4°C and 200´g for 5 min. After the tubes are prepared, in order to select the basophil and measure the activity before starting to work in flow cytometry, the cells are stained with 20 μL monoclonal anti-human IgE, 10 μL monoclonal CD63, and 10 μL CD203C antibodies on ice for 20 min (9)(10)(11)(12)(13)(14). Then, the tubes are worked on in the flow cytometry.…”
Section: Basophil Activation Test: How Is the Activation Of In Vitro mentioning
confidence: 99%
“…Sometimes, they are used together in the evaluations. It is known that the sensitivity and specificity of BAT increase when they are used together (9)(10)(11)(12)(13)(14).…”
Section: Basophil Activation Test: How Is the Activation Of In Vitro mentioning
confidence: 99%
“…Upregulation time-course of these markers seems to be rather tricky to evaluate the quality and the amount of basophil activation response to an IgEmediated triggering agent. In the work of Sturm and colleagues, CD63 and CD203c upregulation are affected both by activation time and by prestoring blood samples at room temperature at different times (1). This observation raises the question whether it is possible to standardize a basophil resting (nonactivated) condition and to evaluate the amount of expression of membrane markers with a reference standardized evaluation, which could be used in any circumstance: in this context, critical factors are represented by basophil spontaneously induced activation, by intracellular calcium and the presence of calcium chelators in the medium, and by time and temperature.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Therefore, it is very important to detect specific antigens (also called allergens) and/or the sensitivity of IgE to the antigens, which induce allergic reactions in each patient. Various diagnostic tests for type I allergy, such as the detection of serum IgE, histamine release from basophils, or skin reactions to allergens, are performed [10][11][12][13][14][15][16][17]. In order to detect antigen-specific IgE in serum, ImmunoCAP TM , Ala-STAT TM , and AD-VIA Centaur TM have been developed and utilized in clinical practices [10].…”
Section: Introductionmentioning
confidence: 99%
“…Griese et al reported that the histamine release test showed higher sensitivity and specificity than the skin test or serum analysis, such as ImmunoCAP TM , based on the comparison with bronchoprovocation of extrinsic asthmatic children [14]. Moreover, BAT based on CD203c upregulation has been validated as a reliable tool for the diagnosis of IgE-mediated allergies [15]. However, HRT requires a substantial quantity of blood for multiple tests, making such testing impractical to perform for babies and infants in clinical practices.…”
Section: Introductionmentioning
confidence: 99%